Spatial regulation of contractility by Neuralized and Bearded during furrow invagination in Drosophila - Gantas Perez-Mockus (Nature Portfolio, 2017)
In the Drosophila embryo, increased cortical contractility in ventral cells causes furrow formation and gastrulation. Here, the authors show that contractility is regulated by Neuralized (an E3 ubiquitin ligase) in ventral cells, and that inhibiting this process with Bearded in the ectoderm causes furrow invagination.